NEGATIVE IMPACTS OF CHANGING LEARNING PATTERNS DURING THE COVID-19 PANDEMIC IN PAI LEARNING AT SMPN SELANGIT MUSI RAWAS - Yesi Arikarani; Abdul Hakim; Fitriyani Fitriyani; Taufik Mukmin; Muhammad Faizul Amirudin (TA'DIB: JURNAL PENDIDIKAN ISLAM, 2022)
The purpose of the study was to determine the transformation of learning patterns and analyze the negative impact of changes in learning patterns during the pandemic in PAI learning at SMP Negeri Selangit Musi Rawas. The method used is qualitative field research, data obtained from in-depth interviews, observations, and documentation. The results showed the application of combination learning (online and offline), the negative impact of changes occurred on teachers, and learning activities were less effective, due to limited time. for students, the affective, cognitive, and psychomotor aspects of students decrease, because the learning system emphasizes students learning individually with minimal supervision and guidance, less effective learning, lack of mobile communication tools, and poor internet access.